The Use of Indirect Corrective Feedback for Improving Written Production (2017)
ABSTRACT: This action research study explores the extent in which Indirect Corrective Feedback (ICF) contributes to improve sixth graders’ written production in a public institution in Medellin, Colombia. The students receive Indirect Corrective Feedback proposed by Ghandi and Maghsoudi (2014, p. 55) in one of the three writing process phases suggested by Strömquist (as cited in Ariyanti , 2016, p. 266), namely: pre-writing, drafting and revising. I used a reflective log and three students’ artifacts as data collection techniques. The findings revealed that the students improved their written production in the reduction of errors and in their positive attitude towards class activities.